Proceedings of SPE/IADC Drilling Conference 1993
DOI: 10.2523/25750-ms
|View full text |Cite
|
Sign up to set email alerts
|

North Sea Advances in Extended Reach Drilling

Abstract: This paper descnbes strategies and techniques employed to extend the drilling reach in the Gullfaks field, offshore Norway. Field development plans were originally based upon deviated wells drilled to a maximum inclination of 60°and a maximum displacement of 3 kID. Emerging horizontal drilling techniques encouraged a reevaluation of these field development plans. These techniques are now being implemented to increase the inclination and extend the reach to 5 kID in support of the revised plan. The early succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Extended Reach Drilling (ERD) is a technique to drill directional/horizontal wells beyond the routine capabilities of drilling rigs and tools. ERD was initiated in 1980's and rapidly evolved during the 1990's [1][2][3][4]. Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD).…”
Section: Introductionmentioning
confidence: 99%
“…Extended Reach Drilling (ERD) is a technique to drill directional/horizontal wells beyond the routine capabilities of drilling rigs and tools. ERD was initiated in 1980's and rapidly evolved during the 1990's [1][2][3][4]. Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD).…”
Section: Introductionmentioning
confidence: 99%